LEARNING ABOUT APPLICATION FOR STUDENT'S GLOBAL WARMING SENIOR HIGH SCHOOL USING MACROMEDIA FLASH 8.0 - Irawan Sapto Aji; Melani Dewi Lusita, SKom, MMSI Melani Dewi Lusita, SKom, MMSI (Jurnal Sistem Informasi, 2009)
This scholarly writing consists of an Application Learning About Global Warming.This application is made to provide learning and knowledge about the causes ofglobal warming and the consequences of global warming, especially for students atthe high school level.In this scientific writing, Applications Learning About Global Warming author usingMacromedia Flash 8.0 which will support the presentation of the learning method inthis application include the use of text, images, motion and accompanied by a voicethat can be expected to attract more users in learning about global warming.